RESULTS OF ALFALFA BREEDING ON PRODUCTIVITY - S. A. Ignatiev; T. V. Gryazeva (Зерновое хозяйство России, 2018)
The main parameter of the breeding work with alfalfa in the ARC “Donskoy” is the improvement of fodder and seed productivity. Through the years the breeding work was carried out with 500–860 collection samples of alfalfa, alfalfa hybrids and alfalfa lines of the local origin. The main method of the breeding work was poly-crossing. It’s characterized with a multiple repetition of selections of the best plants from the populations, their self-pollination and crossing by free pollination in the plots of poly-crossing. It resulted in accumulation and concentration of favourable traits in the population. The selection promoted systematic improvement of synthetic populations according to economic-valuable traits, especially fodder and seed productivity. During the research, productivity of green mass of the standard variety ‘Rostovskaya 90’ was 28.2 t/ha in the first cutting and 19.0 t/ha in the second one on average. The varieties ‘Lyutsiya’ and ‘Selaynka’ produced 30.6 t/ha, 19.8 t/ha and 32.1 t/ha, 20.4 t/ha respectively. The sum of the harvested green mass of the standard variety was 47.2 t/ha, while ‘Lyutsiya’ produced 50.5 t/ha and ‘Selaynka’ 53.1 t/ha, that is on 7.0% and 12.5% larger than the standard. The similar result was obtained in productivity of dry matter. The total quantity of dry matter produced by the standard variety was 11.6 t/ha (two cuttings), the varieties ‘Lyutsiya’ and ‘Selaynka’ gave 12.6 t/ha and 12.8 t/ha that is on 8.6% and 10.3% more than the standard. The estimation of the breeding work with alfalfa in the preliminary and competitive variety testing allowed to identify the new alfalfa variety ‘Golubka’ and to send it to the State Variety Testing. In the competitive variety testing (2012–2016) the variety produced larger yields that the standard variety (productivity of all five 1-st cutting). With its average productivity of green mass (31.9 t/ha) it exceeded the standard on 13.1%. In the 2-d cutting its green mass productivity was 20.9 t/ha that is on 10.9% more that the standard.  With the average productivity of green mass the variety ‘Golubka’ produced 8.0 t/ha in the 1-st cutting and 4.9 t/ha in the 2-d, that is on 12.7% and 8.9% lager that that of the standard.  The variety ‘Golubka’ produced 52.8 t/ha green mass for two cuttings and 12.8 t/ha dry matter that is on 11.9% and 10.3% larger than the standard variety ‘Rostovskaya 90’. Seed productivity of the standard variety was 0.23 t/ha on average, the varieties ‘Lyutsiya’ and ‘Selaynka’ gave 0.25 t/ha, the new variety ‘Golubka’ produced 0.29 t/ha, that is on 8.7 and on 26.1% more than the standard.